The nature and origin of magnetic anomalies over the Gölcük caldera; Isparta; South-Western Turkey - Dolmaz, M.N.; Oksum, E.; Erbek, E.; Tutunsatar, H.E.; Elitok, O. (Геофизический журнал, 2018)
For the first time; ground magnetic survey was performed which data were inverted by means of total horizontal derivative; horizontal gradient analytic signal; and hyperbolic tilt angle techniques to identify subsurface volcanic structures around Isparta city (South-Western Turkey). Впервые проведена магнитная съемка, данные которой были преобразованы методами полной горизонтальной производной (ПГП), обнаружения аналитического сигнала горизонтального градиента (АСГГ), определения угла гиперболического наклона (УГН) для идентификации погребенных вулканических структур вокруг г. Испарта (юго-западная Турция). Вперше проведена магнітна зйомка, дані якої були перетворені методами повної горизонтальної похідної (ПГП), виявлення аналітичного сигналу горизонтального градієнта (АСГГ), визначення кута гіперболічного нахилу (УГН) для ідентифікації похованих вулканічних структур навколо м Іспарта (південно-західна Туреччина).